2015
DOI: 10.1016/j.contraception.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Young men’s awareness and knowledge of intrauterine devices in the United States

Abstract: Title3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Though many claim awareness of the IUD, they failed to understand its function or its side effects. The results of this study were similar to the 2015 study performed by Marshall et al, which found that awareness and perceived knowledge of IUDs among males was low in comparison to condoms and birth control pills (12). However, the same study has also shown that young men's perceived knowledge of IUDs was lower than their objective knowledge, whereas this study revealed that most males did not know much about the utility of the IUD (12).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Though many claim awareness of the IUD, they failed to understand its function or its side effects. The results of this study were similar to the 2015 study performed by Marshall et al, which found that awareness and perceived knowledge of IUDs among males was low in comparison to condoms and birth control pills (12). However, the same study has also shown that young men's perceived knowledge of IUDs was lower than their objective knowledge, whereas this study revealed that most males did not know much about the utility of the IUD (12).…”
Section: Discussionsupporting
confidence: 87%
“…In a 2012 study done by Barrett et al, they found that only 39.4% of subjects who had heard about the IUD were able to identify its features (12). Awareness and perceived knowledge of IUDs among males is low in comparison to condoms and birth control pills (12). Since male partners can influence the contraceptive decision-making process, it is important that studies are done to understand their perspectives.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…In a US nationally representative sample, more than half of young men knew little or nothing about hormonal methods [5]. Knowledge among these young men about intrauterine devices, a form of LARC, is even lower than knowledge about oral contraceptive pills (OCPs) [17]. In fact, a US qualitative study of 41 young men found 54% incorrectly consider OCPs as the ‘most effective’ contraceptive method, whereas 10% correctly categorize intrauterine devices as the ‘most effective’ [13].…”
Section: Young Men’s Knowledge Of Contraceptionmentioning
confidence: 99%
“…This result shows that the concept of gender equality in men needs to be improved. Male attitudes are significant predictors of contraceptive use (15) and ensuring the participation of males significantly increases the use of modern FP methods (16) . While studies have indicated that males and females alike should take responsibility in regards to the use of FP methods, male participation in FP services was found to be limited and the use of contraceptives was regarded as being the responsibility of female partners (9,19,22,26) .…”
Section: Discussionmentioning
confidence: 99%
“…So, many of the studies conducted to evaluate knowledge and attitudes about FP in these countries usually focus on married individuals, as well as on women (3,4,(9)(10)(11)14) . However, male attitudes are significant predictors of contraceptive use (15) , and ensuring the participation of males in FP planning significantly increases the use of modern FP methods (16) .…”
Section: Introductionmentioning
confidence: 99%